Greek Catenae and the “Western” Order of the Gospels - Patton, Andrew J. (Novum Testamentum, 2022)
The “Western” order of the gospels—Matthew–John–Luke–Mark—is found in a few important ancient codices in both the Greek and the Latin tradition. Previous attempts to identify Greek minuscule manuscripts with this sequence have been inconclusive. This article presents five Greek minuscules which feature the gospels in the Western order. These five manuscripts, along with two Greek majuscules, contain the earliest form of the catena commentary on Matthew, John, and Luke. The analysis of these catenae reveals that the sequence of their composition is reflected in the codicology of these manuscripts, as well as non-standard orders of the gospels in other catena witnesses. It is therefore the presence of the commentary which explains the adoption of the Western order in seven of the eleven known occurrences in Greek.